Cigarette smoking is a modifiable risk factor for Barrett's oesophagus. Issue 6 (1st December 2013) - Balasubramanian, Gokulakrishnan; Gupta, Neil; Giacchino, Maria; Singh, Mandeep; Kanakadandi, Vijay; Gaddam, Srinivas; Wani, Sachin B; Higbee, April D; Rastogi, Amit; Bansal, Ajay; Sharma, Prateek
Abstract : Background: Cigarette smoking has been associated with an increased risk of oesophageal adenocarcinoma (OAC). However, the impact of smoking and more importantly smoking cessation on Barrett's oesophagus (BO) is unclear. Objective: The aim of the study is to evaluate the association between cigarette smoking and presence of BO in a large prospective cohort of patients with gastro‐oesophageal reflux disease (GORD). Methods: Patients presenting to the endoscopy unit for upper endoscopy completed a validated GORD questionnaire and information on demographics (age, gender, and ethnicity), cigarette smoking [status (current/past), amount (pack years) and duration of smoking cessation], clinical data [medication history, body mass index (BMI), and family history] and endoscopic findings [BO and hiatal hernia] were recorded. Cigarette smokers (current and past) and nonsmokers were compared using Fisher's Exact test for categorical variables and Mann–Whitney test for continuous variables. Effects of cigarette smoking and smoking cessation on BO risk was assessed by stepwise logistic regression analysis. Results: A total of 1056 patients were included in the analysis [mean age: 57.2 ± 12.7years, Caucasian 880 (83.3%), male 985 (93.3%), and mean BMI 29.6 (SD: ± 5.6)]. 827 (78.3%) were smokers and 229 (21.6%) were nonsmokers. 474 subjects (44.9%) had a previous history of smoking. Anytime smokers were more likely to have BO (adjusted OR: 3.3; 95 CI: 1.7–6.3; p < 0.01). Higher smoking burden (pack years) was associated with higher risk of BO in this GORD cohort ( p for trend < 0.01). Duration of smoking cessation was inversely associated with risk of BO ( p for trend: 0.01). Conclusion: This study shows that smokers with reflux symptoms have about threefold higher risk of BO compared with nonsmokers, whereas discontinuing smoking is associated with a significant reduced risk. Smoking cessation appears to be a viable option to reduce BO risk in patients with reflux disease.